Cushion plants act as facilitators for soil microarthropods in high alpine Sweden - Peter Ľuptáčik (14150913) (2022)
Cushion plants can have positive impacts on plant richness in severe environments and possibly across trophic levels on arthropods, an under-studied topic. This study examined whether soil communities under cushions have higher richness and abundance of soil microarthropods than adjacent non-cushion vegetation, and whether differences in collembolan and mite abundance and species richness between cushions and adjacent vegetation increase with elevation. Paired soil samples were taken under cushions of Silene acaulis along the elevation gradient (1000, 1100, 1200, 1300, 1400 m a.s.l.), under cushions of Diapensia lapponica on the exposed ridge above the treeline (1000 m a.s.l.), and under adjacent non-cushion plant vegetation. In total, 5853 individuals of collembolans (n = 1705) and mites (n = 4148) were obtained from soil samples and identified to order/species level. S. acaulis cushions had a positive effect on species richness and abundance of collembolans, with richness effects from 1100 m a.s.l. upwards. Oribatid mite richness and abundance were also higher under cushions compared with adjacent vegetation. Species richness of collembolans and oribatids declined with increasing elevation from 1200 m a.s.l. Collembolan abundance peaked at mid-elevation (1200 m a.s.l.) under cushions and adjacent vegetation, while oribatid mite abundance peaked at 1300 m a.s.l. under both vegetation types. D. lapponica cushions on the exposed ridge had significant positive effects on species richness, abundance and diversity index of collembolans, and abundance of oribatids. Cushion plants play an important role in supporting the biodiversity of soil fauna in severe alpine environments, with the positive effects of cushion plants increasing with environmental severity. Other Information Published in: Biodiversity and Conservation License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10531-021-02247-y